Clinical appearance of preeclampsia repetition and prognosis - García Valenzuela, Raúl (2015)
Repeat preeclampsia, preeclampsia mode that offers own contours, is not debatable clinical reality. You can take different expressions -within the wide range of shades of this particular picture grávido- state and its retrograde symptoms to disappear definitively, once produced childbirth. When the hypertensive syndrome dominates the scene, the acute vascular events can trigger seizures and generate bleeding in the utero-placental territory, own these accidents of preeclámpticos states. EI differential diagnosis with pre-existing hypertensive disease is often difficult and a thorough exploration ratify the anatomical indemnity of the cardiac silhouette, with normal renal function tests, absence of retinal arteries sclerosis, etc. it will be needed In general it can be accepted that while the old processes do hatch in the first half of pregnancy, aggravating it from its early stages, the appellant toxemia as one that appears first intention is late and announced in the last quarter, although by exception may explode prematurely, interfering in a time that is not their specific domain. Action despite repeated impacts, usually evolves as genuinely repeatedly gravidarum disease, while their final anatomical ions. As all toxemia, however, it may be the point of origin of definitive vascular disease is glomerulonephritis or chronic essential hypertension; this group represented a 13.3%. EI forecast, according to the experience of others and of the author, and is kind, without being subject to the sometimes noisy symptoms and possible accidents. Indeed, despite the inherent effects of recurrent disease (2 to 3 times) -37 pregnancies from 15 patients-group mortality was 0%, considering that in the same period mortality generated: by preeclampsia it reached 1.1 %. Fetal perinatal mortality, however, was significant (35.1%), mainly in older women, where it reached 78 .5%.